The Effect of Work-Life Balance on Generation Z Productivity: The Mediating Role of Employee Engagement among Part-Time Working Students in Jakarta - Budiman Budiman; Asep Suherman (SEAN Institute, 2026)
The increasing participation of Generation Z university students in part-time employment has intensified the challenge of balancing academic responsibilities, work commitments, and personal life, making work-life balance an important factor influencing employee productivity. This study aims to examine the effect of work-life balance on Generation Z productivity, with employee engagement serving as a mediating variable among part-time working students in Jakarta. A quantitative research approach with a cross-sectional survey design was employed. Data were collected through an online questionnaire from 168 Generation Z university students in Jakarta who met the predetermined sampling criteria using purposive sampling. The measurement instrument consisted of 21 indicators adapted from established scales and was assessed using a seven-point Likert scale. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 3.0. The results indicate that work-life balance has a positive and significant effect on employee engagement and Generation Z productivity. Employee engagement also exerts a significant positive effect on productivity and partially mediates the relationship between work-life balance and productivity. The structural model explains 50.8% of the variance in Generation Z productivity, demonstrating moderate predictive power. These findings suggest that organizations and higher education institutions should promote flexible work arrangements, supportive supervision, and employee well-being initiatives to strengthen employee engagement and improve the productivity of Generation Z part-time working students.